The correlation between self-efficacy and peer interaction towards students’ employability in vocational high school - Fatwa Tentama; Muhammad Zulfikar Nur (International Journal of Evaluation and Research in Education (IJERE), 2021)
Employability is an important factor that can determine the quality of prospective graduates, especially in vocational high schools. Therefore, vocational high schools, as one of the educational institutions that prepare workforce resources, need to pay attention to factors that can increase their students' employability. This study aims to empirically examine the role of self-efficacy and the peer interaction on student employability. The subjects of this study were 132 students at Vocational High School Muhammadiyah Prambanan. The data were collected through an employability scale, a self-efficacy scale, and a peer interaction scale. The data were then analyzed with multiple linear regression techniques. The results showed that: 1) Simultaneously, there was a very significant role that self-efficacy and peer interaction have on employability with p=0.000 (p<0.01); 2) Partially, there was also a very significant role that self-efficacy has on employability with p=0.000 (p<0.01); 3) Peer interaction also had a partially significant role on employability with p=0.001 (p<0.01). Both self-efficacy and peer interaction simultaneously contributed 40.8% to employability, but self-efficacy had a more dominant role (26.7%) than peer interactions (14.1%).